Enterococcus spp. Indicator of Fecal Pollution is Detected by Classical and Molecular Methods from Recreation Areas in Caddebostan (Istanbul) - (:unkn) unknown (FOUNDATION ENVIRONMENTAL PROTECTION & RESEARCH-FEPR, 2011)
Caddebostan beaches are one of the most important recreational area in Anatolian side of Istanbul. Microbiologically investigation of fecal contaminants will be most important for public health. In our study, we aim to investigate Enterococcus spp. that marked of the source of fecal pollution in autumn (October), winter (January), and especially summer (June, July, August) by culture-based traditional and molecular methods such as plate count and Q-PCR method respectively. Enterococcus spp. expressed at last 8 days of fecal pollution because of its resistant in literature. Fecal pollution may be changed with some parameters such as weather, precipitation (snow, raining, vs.), wind. Because of this reason, including the day of the sample collected until the 8 days before the sample collection date reports of the weather was compared with results from the samples. The number of Enterococcus spp. was accelerated in summer months. Logarithmic positive correlation was found between classical and molecular methods.
Keywords: Enterococcus spp.; Fecal pollution; Plate count methods; Q-PCR; QUANTITATIVE PCR; DRINKING-WATER